Lophosceles Ringdahl 1922 - Sorokina, Vera S.; Pont, Adrian C. (Zenodo, 2010)
Genus Lophosceles Ringdahl, 1922 Lophosceles Ringdahl, 1922: 3. Type-species: Musca mutata Fallén, 1825, by original designation. Lophosceles cinereiventris (Zetterstedt, 1845) Aricia cinereiventris Zetterstedt. 1845: 1500. Type-locality: Sweden, Jämtland, Skalstugan. Holotype ♂, MZLU (Pont, in press). Siberian records: Respublika Altay (Sorokina, 2006b: 139). General distribution: Holarctic Region; in the Palaearctic, from Europe east to China. Lophosceles frenatus (Holmgren, 1872) Aricia frenatus Holmgren, 1872: 103. Type-locality: not stated (from title: Nordgrönland, actually N W Greenland, Nordfjord). Syntypes 2♂, NHRS (seen). Siberian records: Pripolar Urals, Mt. Neroika (Malozemov, 1992: 92). General distribution: Holarctic Region; in the Palaearctic, from montane and northern Europe, Russia (north-west European Russia, West Siberia) and China. Lophosceles hians (Zetterstedt, 1838) Anthomyza hians Zetterstedt, 1838: 698. Type-locality: Finland, Lapland, Muonioniska. Lectotype ♀, MZLU (designated by Pont, in press). Siberian records: West Siberia (Pont, 1986a: 135). General distribution: Holarctic Region: Northern Europe, Russia (north-west European Russia, West Siberia) and Alaska. : Published as part of Sorokina, Vera S. & Pont, Adrian C., 2010, An annotated catalogue of the Muscidae (Diptera) of Siberia 2597, pp. 1-87 in Zootaxa 2597 (1) on page 40, DOI: 10.11646/zootaxa.2597.1.1, http://zenodo.org/record/5318926 : {"references": ["Ringdahl, O. (1922) Tva nya anthomyidslakten. Entomologisk Tidskrift, 43, 1 - 4.", "Zetterstedt, J. W. (1845) Diptera Scandinaviae disposita et descripta. [Part.] Tomus quartus. Ex officina lundbergiana, Lundae [= Lund], pp. 1281 - 1738.", "Sorokina, V. S. (2006 b) Contributions to the knowledge of the house-flies (Diptera, Muscidae) of the mountain Altay. In: Materials of the meeting of Siberian and Far East entomologists \" The entomological research in Northern Asia \". Institute of Systematics and Ecology of Animals of Russian Academy of Sciences, Siberian Branch, Novosibirsk, pp. 138 - 140. [In Russian.]", "Holmgren, A. E. (1872) Insekter fran Nordgronland, samlade af Prof. A. E. Nordenskiold ar 1870. Ofversigt af Kungliga Vetenskaps-Akademiens Forhandlingar, Stockholm, 29, 97 - 105.", "Malozemov, A. Yu. (1992) On the fauna and ecology of true flies (Diptera, Muscidae) of the eastern macroslope of the Pripolar Ural Mountains. In: Nikolaeva, N. V. (Ed.), Insects in natural and anthropogenic biogeocenozes of the Urals. Nauka, Yekaterinburg, pp. 91 - 93. [In Russian.]", "Zetterstedt, J. W. (1838) Sectio tertia. Diptera. In: Insecta Lapponica. \" 1840 \", Leopold Voss, Lipsiae [= Leipzig], pp. 477 - 868.", "Pont, A. C. (1986 a) Family Muscidae. In: Soos, A. & Papp, L. (Eds), Catalogue of Palaearctic Diptera. Volume 11. Scathophagidae - Hypodermatidae. Akademiai Kiado, Budapest, pp. 57 - 215."]}